Efektivitas Proprioceptive Neuromuscular Facilitation Terhadap Kemampuan Motorik Wajah Pasien Bell’s Palsy: Case Report - Dinda Ayudya Puspitaningrum; Isnaini Herawati; Eko Prihati; Farid Rahman (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Introduction: Bell's palsy or also known as idiopathic facial nerve paralysis is a common type of facial muscle weakness caused by lesions of the cranial nerve facialis (VII). One of method that can be used to treat Bell's palsy is Proprioceptive neuromuscular facilitation (PNF). PNF can facilitate neuromuscular performance to accelerate healing from Bell's palsy and improve facial muscles including strength, flexibility, and coordination. Objective: to proved the effectiveness of PNF on the motor control ability of Bell's palsy. Methods: Single subject research conducted on an 18 year old teenager with Bell's palsy. Subjects were given exercise using the PNF method for 4 weeks which was carried out 2x/week and motor evaluation was carried out at the end of the study. Results: The evaluation was carried out using the Manual Muscle Testing and Ugo Fisch Scale. At baseline, facial muscle strength is worth 1 which means it has minimal contraction, after 8 treatment sessions there is an increase in muscle strength to 5 and some muscles are worth 3. Facial functional measurements using the Ugo Fisch Scale at baseline had a total score of 38 then after being given treatment for 4 weeks it increased to 76 Conclusion: There was an increase in motor function in the form of muscle strength and facial function in Bell's palsy patients after being given training with the PNF method for 4 weeks.Keywords: Bell’s Palsy, Exercise, Facial Nerve, Motoric, Proprioceptive Neuromuscular Facilitation